Ms. Marvel. [Vol. 1] Best of the best - Reed, Brian 1973-; Torre, Roberto de la.; Palmiotti, Jimmy; Sotomayor, Chris; Sharpe, Dave.; Steven Rothman Collection of Comics, Cartoons, and Graphic Novels (University of Pennsylvania); Comics Collection (University of Pennsylvania) (New York Marvel Comics, 2007)
Carol Danvers has been known by many names; most recently, she's called herself Captain Marvel. Now, however, she re-adopts the name Ms. Marvel and decides that it's time she lived up to the name. On the way to earning the name, she settles a score with the evil Brood, prevents an invading alien from destorying the Earth, and fights off a mad magician from another reality.
"Contains material originally published in magazine form as Ms. Marvel #1-5 and Giant-size Ms. Marvel #1"--Cover p. [2].
Keywords: Women heroes -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Science fiction comic books, strips, etc; CHR 2007.; PRO Rothman, Steven D. (donor)